Description of last instar nymph of Zoraena sarracenia (Abbott & Hibbitts, 2011) (Odonata: Cordulegastridae) with notes on its life history - Abbott, John C.; Tennessen, Kenneth J. (Zootaxa, 2026)
The last instar (F0) nymph of Zoraena sarracenia (Abbott & Hibbitts, 2011) (Odonata: Cordulegastridae) is described for the first time based on 34 lab-reared and field-collected specimens from Texas and Louisiana. Diagnostic morphological characters, measurements, and setal counts are provided, and the nymph is compared with other members of the diastatops species group. Characters useful for identification include premental structure, labial dentition and setation, and setae along the posterior margin of the compound eyes. Notes on habitat, distribution, and life history are presented based on field observations and laboratory rearings. The species inhabits small, boggy rivulets and seepages, often associated with pitcher plant (Sarracenia alata) bogs, but also occurs in shaded seepage habitats. Laboratory rearings suggest a minimum nymphal development time of approximately two years, with some individuals requiring three years. This description completes knowledge of nymphal morphology within the diastatops species group and facilitates identification and conservation assessment of this geographically restricted species.